The Level of Zinc is Increasing, while the Serum Folat Level is Decreasing, after Multi-Micronutrient Supplementation in Pregnant Woman - Noroyono Wibowo (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To measure the changes of serum iron, folic acid, zinc and selenium level on pregnant woman after multi-micronutrient supplementation. Method: First trimester pregnant woman whom attended Maternal- Fetal Policlinic at Dr. Cipto Mangunkusumo Hospital from July 2011 till October 2011 was considered into the study. The intervention was consumption of multi-micronutrient tablet once a day for three months period. The outcomes were the measurements of serum level of iron, folic acid, zinc and selenium before and after supplementation. We used paired T Test and Wilcoxon test for statistical analysis. Results: Twenty-eight pregnant women in their first trimester participated in the study. The micronutrient serum level was measured before and after supplementation during the time period. Before supplementation, serum iron and zinc level were below normal. Serum selenium level was normal with higher than normal serum folic acid level. After supplementation, serum zinc level was found to be below normal. Both level of serum iron and selenium increased to normal. Serum folic level was higher than normal. We found a decrease in serum zinc level with an increase in serum folic acid level that was statistically significant (p 0.009; p 0.003 respectively). We also found a slight decrease of serum iron level and an increase of serum selenium level that were not statistically significant (p 0.295; p 0.333). Conclusion: There is a decreased level of serum zinc with an increase in serum folic acid level after multi-micronutrient supplementation. [Indones J Obstet Gynecol 2012; 36-4: 171-5] Keywords: multi-micronutrient, supplementation